EFEKTIFITAS NIGHT AUDITOR DAN HUBUNGANNYA DENGAN PENGENDALIAN INTERN PADA HOTEL BINTANG LIMA - Suarsa Darma Putra, I Made; Karya Utama, I Made (E-Jurnal Akuntansi, 2014)
Night auditor is responsible for the correctness and accuracy of data entry of sales in one day. The problem is, there is often lack of clarity of roles and functions of the effectiveness of night auditor at several hotels including the five-star category. Research with quantitative analysis techniques using non-parametric statistical hypothesis is put forward there is a relationship between the effective functioning of the internal control auditor night at five-star hotels in Badung regency. The results obtained that the function of night auditor at a five-star hotel in Badung including highly effective category. In addition there is a relationship between moderate or moderately effective functioning of the internal control auditor night at five-star hotels in Badung regency
Keywords: effectiveness, night auditor, internal control